Self‐Hydrophobization in a Dynamic Hydrogel for Creating Nonspecific Repeatable Underwater Adhesion. (20th December 2019) - Han, Lu; Wang, Menghao; Prieto‐López, Lizbeth Ofelia; Deng, Xu; Cui, Jiaxi
Abstract: Adhesive hydrogels are widely applied for biological and medical purposes; however, they are generally unable to adhere to tissues under wet/underwater conditions. Herein, described is a class of novel dynamic hydrogels that shows repeatable and long‐term stable underwater adhesion to various substrates including wet biological tissues. The hydrogels have Fe 3+ ‐induced hydrophobic surfaces, which are dynamic and can undergo a self‐hydrophobization process to achieve strong underwater adhesion to a diverse range of dried/wet substrates without the need for additional processes or reagents. It is also demonstrated that the hydrogels can directly adhere to biological tissues in the presence of under sweat, blood, or body fluid exposure, and that the adhesion is compatible with in vivo dynamic movements. This study provides a novel strategy for fabricating underwater adhesive hydrogels for many applications, such as soft robots, wearable devices, tissue adhesives, and wound dressings. Abstract : Underwater adhesion is achieved through a self‐hydrophobization process on a dynamic hydrogel surface. The adhesion mechanism ensures ready, strong, nonspecific, repeatable, and long‐term stable underwater adhesion without requiring extra processes or reagents, which enables convenient application underwater/or in wet conditions.